2018
DOI: 10.21037/tau.2017.12.34
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in active surveillance and the associations with decision-making—a literature review

Abstract: Several studies have been conducted on the quality of life (QoL) in men with low risk prostate cancer (PCa) who choose active surveillance (AS). While recent reviews have shown a lack of consistency among the available QoL-studies, a few key points have been identified, including decision-making (DM)-related issues and their potential effect on QoL. The importance of this theme has also been recently highlighted by the international task force of the European School of Oncology. However, to our knowledge, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 46 publications
(75 reference statements)
0
14
0
Order By: Relevance
“…AS protects against QOL impairments relative to curative treatment for PCa. However, a small proportion of men may experience disease‐related psychological morbidity early on during AS, which can negatively impact overall QOL . In men undergoing curative treatment for PCa, higher PA levels are associated with less distress and greater QOL .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AS protects against QOL impairments relative to curative treatment for PCa. However, a small proportion of men may experience disease‐related psychological morbidity early on during AS, which can negatively impact overall QOL . In men undergoing curative treatment for PCa, higher PA levels are associated with less distress and greater QOL .…”
Section: Discussionmentioning
confidence: 99%
“…We found that 13.6% of patients exhibited low EWB early on AS. Previous literature suggests that psychological morbidity can impact treatment decisions in men with low‐risk disease . Therefore, it is important for health care practitioners to identify men with low EWB early on AS and subsequently recommend strategies (eg, PA) to foster their support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our review did not find any evidence of the use of QoL assessment within the treatment-strategy-decision-making process for ACS patients. This is despite studies in other disease areas emphasising the importance of, and recommending the, measuring QoL for decision making for therapeutic preferences [63][64][65][66][67][68][69][70]. For example, Sutherland and Till [63] emphasised the importance of assessing QoL at different levels of decision making: (i) at micro-level to help ACS patients participate in the decision making process relating to their preferred treatment/s), (ii) at meso-level to benefit groups at agency, institution or regional network level (e.g., teams of cardiologist may take part in developing protocols for management of ACS or small agencies working on ACS management), and (iii) at macro-level to benefit the population in general (e.g., the baseline data about QoL may help to the government to design population-level policy).…”
Section: Meta-analysis Of Status Of Qol Among Acs Patients At Baselinmentioning
confidence: 99%
“…[5][6][7] The latter is therefore also an important factor when treatment choices have to be made. [8][9][10][11] Both the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) highly endorse the use of patient-reported outcomes (PROs) in this context by requiring the integration of the patients' perspective through better reporting of adverse events and HRQoL in randomized controlled trials (RCTs). 12,13 However, several systematic reviews have highlighted that a high proportion of RCTs including PROs poorly report on these measurements, with missing information being very common.…”
Section: Introductionmentioning
confidence: 99%